ANALYSIS OF INTERNATIONAL BOYCOTT ON STOCK PERFORMANCE AND VALUE OF MANUFACTURING COMPANIES ON THE IDX - Wiwit Anisa; Nursetiana, Herni; Yudha Pratama, Versiandika (Berkala Akuntansi dan Keuangan Indonesia, 2025)
This study aims to analyze the impact of international boycotts on stock performance and corporate value of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The method used in this study is a quantitative study with an event study approach, which analyzes market reactions to the boycott event after the issuance of MUI Fatwa No. 83 of 2023 on November 8, 2023. The data used include stock values ​​from Yahoo Finance, trading volume data, and quarterly financial reports of companies published on the IDX. The research sample was taken using a purposive sampling technique, focusing on companies affiliated with Israel that experienced a boycott. The data analysis technique used a normality test, significance test, and paired t-test. The results of this study indicate that the boycott did not have a significant effect on the stock performance of the affected companies, with no decrease in abnormal returns and TVA in the 15-day period after the boycott announcement. In addition, there was no significant decrease in company value, as measured by profitability, namely Return on Assets (ROA). Meanwhile, in measuring liquidity, namely the Current Ratio (CR), there was a significant decline in companies experiencing boycotts.